2015
DOI: 10.2196/mhealth.4924
|View full text |Cite
|
Sign up to set email alerts
|

Health App Use Among US Mobile Phone Owners: A National Survey

Abstract: BackgroundMobile phone health apps may now seem to be ubiquitous, yet much remains unknown with regard to their usage. Information is limited with regard to important metrics, including the percentage of the population that uses health apps, reasons for adoption/nonadoption, and reasons for noncontinuance of use.ObjectiveThe purpose of this study was to examine health app use among mobile phone owners in the United States.MethodsWe conducted a cross-sectional survey of 1604 mobile phone users throughout the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
923
12
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,223 publications
(1,020 citation statements)
references
References 10 publications
69
923
12
16
Order By: Relevance
“…Many have observed the problems but so far no strong evidence has emerged for the right solutions yet. While only 10% of the population are using health-tracking devices/apps to help manage chronic conditions [52], the proportion of US health consumers accessing their health records has increased to 45% in 2016 (an increase of 67% in two years) [53]. The increasing access and connection between clinics and homes have indicated new opportunities in bridging the gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Many have observed the problems but so far no strong evidence has emerged for the right solutions yet. While only 10% of the population are using health-tracking devices/apps to help manage chronic conditions [52], the proportion of US health consumers accessing their health records has increased to 45% in 2016 (an increase of 67% in two years) [53]. The increasing access and connection between clinics and homes have indicated new opportunities in bridging the gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Adults own smartphones and over 12% are "smartphone-only" internet users -who get all of their internet access through a smartphone instead of traditional home broadband services. Over half of U.S. cell phone users report downloading at least one healthrelated app and using them daily (Krebs & Duncan, 2015). A 2015 systematic review (Payne, Lister, West, & Bernhardt) studied the literature on health apps and found the most studies focused on evaluating apps for disease prevention and management, monitoring health behaviors and vitals, content analysis and utility, and user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the Pew Research Center, 72% of internet users say they have searched online for health information [13]. Another recent national study suggests more than half of mobile phone users have downloaded a healthrelated mobile application (henceforth referred to as an app) [14]. These users were also found to place high trust in these apps' accuracy and experienced positive health effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent national study suggests more than half of mobile phone users have downloaded a healthrelated mobile application (henceforth referred to as an app) [14]. These users were also found to place high trust in these apps' accuracy and experienced positive health effects [14]. Despite the frequency and use of these technologies, there is no regulatory authority to validate the legitimacy of health-related content published through these commercial apps, nor is there a mechanism to enforce standards to ensure the information is accessible by diverse populations [15].…”
Section: Introductionmentioning
confidence: 99%